2022
DOI: 10.1155/2022/2088034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking Method on Vitamin C Loses and Antioxidant Activity of Indigenous Green Leafy Vegetables Consumed in Western Uganda

Abstract: Indigenous green leafy vegetables are known to contain high levels of antioxidants and are recommended in the management of chronic diseases. However, their consumption has received lower patronage. This is partly attributed to farmers replacing the growing of indigenous green leafy vegetables with their exotic counterparts and scarce information on their nutritional benefits. This study explored the effect of cooking methods (boiling and steaming for 10 minutes) on the antioxidant activity of Amaranthus dubiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the contrary, the green and yellow lines registered the major decrements with SBP059 showing the highest significant loss (−73.9%) (Figure 4c). As well documented in the literature, the decrease in the antioxidant capacity in vegetables during cooking was attributable to the loss of antioxidants and, in particular, to the drastic reduction in the vitamin C and phenolic contents of the raw materials [59][60][61]. Here, considering the increase in some flavonoid-glucosides contents and the decrease in the TEAC observed after cooking, we can guess that in cooked snap beans, these metabolites do not contribute greatly to the antioxidant activity, and the higher contribution could be attributable to other compounds such as free phenols and vitamins losses by leaching or thermal degradation.…”
Section: Characterization Of the Selected Snap Bean Linesmentioning
confidence: 68%
“…On the contrary, the green and yellow lines registered the major decrements with SBP059 showing the highest significant loss (−73.9%) (Figure 4c). As well documented in the literature, the decrease in the antioxidant capacity in vegetables during cooking was attributable to the loss of antioxidants and, in particular, to the drastic reduction in the vitamin C and phenolic contents of the raw materials [59][60][61]. Here, considering the increase in some flavonoid-glucosides contents and the decrease in the TEAC observed after cooking, we can guess that in cooked snap beans, these metabolites do not contribute greatly to the antioxidant activity, and the higher contribution could be attributable to other compounds such as free phenols and vitamins losses by leaching or thermal degradation.…”
Section: Characterization Of the Selected Snap Bean Linesmentioning
confidence: 68%
“…Vitamin C is heat labile and water−soluble. Thus, significant amounts are lost during food preparation and cooking [ 31 ]. Many examples of Thai cuisine sprinkle fresh mint leaves on top, such as Yam, Larb, and Phla (spicy Thai−style salad); consuming raw mint can provide maximum vitamin C.…”
Section: Discussionmentioning
confidence: 99%
“…CUPRAC and FRAP values of raw and cooked Trachystemon orientalis (L.) G. Don plants are provided in Table 1, and DPPH values are presented in Fig 2 . When the antioxidant activity of Trachystemon orientalis (L.) G. Don was evaluated, and it was observed that the CUPRAC value was 138.86±5.17 mmol trolox/g DW, the FRAP value was 44.74±0.59 μmol Fe (II)/g DW, and DPPH value was 0.43±0.33 mg/mL. When CUPRAC, FRAP and DPPH values were examined in many studies, it was found that the antioxidant activity of raw Trachystemon orientalis (L.) G. Don plant was higher than many plants in nature [32][33][34][35][36][37]. The average CUPRAC values of Hypericum montbretii, Paliurus spina-christi Mil and Hypericum bupleuroides were determined to be 1.07±0.14-0.19±0.05 mmol trolox/g DW [32].…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 99%